Assessment Of Motility And Velocity Parameters Of Freshly Ejaculated Spermatozoa Of Bubalus Bubalis And Bos Indicus Bulls Through Computer Assisted Semen Analyzer - Patel, J.B.; Dhami, A.J.; Patel , P.A.; Savaliya , F.P. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Fresh semen ejaculates (90) of 15 mature bulls, 5 each of Jafarabadi, Mehsana and Crossbred (HF x Kankrej) breeds were studied for sperm motility and velocity parameters through computer assisted semen analyzer (CASA). The mean values of motile and progressively motile sperm in the semen of Jafarabadi and Mehsana buffalo bulls were significantly (P<0.05) higher than in crossbred bulls. The average path velocity of buffalo sperms were significantly higher than those in cow bulls. Moreover, semen of Jafarabadi bulls was better than Mehsana buffalo bulls in these regards. Among the mean values of other velocity parameters, viz., amplitude of lateral head displacement (ALH, µm), beat-cross frequency (BCF, Hz), straightness (%), linearity (%), elongation (%) and sperm area (µm2), none differed significantly between Jafarabadi, Mehsana and HF x K crossbred bulls, except BCF, which was significantly (P<0.01) higher for buffalo than in crossbred bulls. The velocity distribution of sperms in terms of rapid, medium, slow motile and static did not differ between Jafarabadi and Mehsana bulls, but the values of rapidly motile sperm in crossbreds were significantly lower and medium motile and static sperm were higher than in buffaloes. Semen of crossbred bulls in general appeared relatively poor than Mehsana buffalo and the Jafarabadi sperms were better in terms of all the traits evaluated through CASA.